Estates of Chilandar’s pyrgos Hrusia (Chryseia) in Kosovo and Metohija in the Middle Ages - Zarković, Božidar V. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The Monastery of Chilandar and his monks, during the first century of existence, encountered various hardships. The big issue for them were the pirates, who often attacked, plundered, took monks into slavery and then sold or ransomed them. Such a problem existed on Mount Athos long vefore St. Sava and and his father Simeon raised Chilandar in 1198. After a turbulent XIII century, which brought frequent changes of borders, King Milutin stabilized the country and its relations with its neighbors, notably Byzantium. The result was a marriage with the Byzantine princess Simonis Palaiologina and obtaining more conquered territories as her dowry. Soon afterwards, he addressed the request of the monks of Chilandar to provide them with some protection against pirates „because their whole life at sea.” Milutin accepted the invitation and early fourteenth century raised their pyrgos Chryseia. The pyrgos was part of Chilandar, which had the obligation to support the monks. Thanks to good relations with the king Milutin, at whose request was probably elected the first abbot, Simeon, the monks of pyrgos began to independently acquire properties. This was helped by Andronikos II and Michael IX, Emperor and Regent of Byzantium, who at the request of their son/brother in law – King Milutin, confirm or give their contributions to the pyrgos. The pyrgos grew stronger and richer, and became independent from the Chilandar monastery, which led to disputes between them. The conflict particularly deteriorated in the second half of the XIV century – after the death of the Emperor Stefan Uroš IV Dušan, culminating in a trial at the court of the Diocese of Serres, in 1388. The judges ruled that the pyrgos was subordinated to the monastery of Chilandar, and that it cannot be independent. By a charter from the period dating from 1336 to 1344, Stefan IV Dušan gave estates in Kosovo and Metohia to the pirgos of Chryseia. These estates consisted of two parts: the first was in Kosovo and included the Church of the Holy Virgin in Lipljan, the village Slovinje with 23 families of dependent people, and the revenues of the market in Lipljan, when it was organized to celebrate the days of the church. A charter describes the boundaries of the village, so we know where that land property was located. It was on the East of Lipljan, between the villages of Gušterica and Smoluša. These villages still exist with the same names. The second part of the estate was located in the North of Metohija, in the area of Metohisjki Podgor. It included half of a vineyard, a piary, a meadow and several large parts of land which were located between the villages of Žakovo, Suvo Grlo, Banje, Rudnik and Kostrc. Since all these villages still exist with the same names, it is easy to determine where the slump was. This slump was managed by the oikonomos, which means it was unique. These estates were confirmed by the Emperor Dušan in the General Chilandar charter of 1348. This ruler gifted the pyrgos with 1000 perpera of silver from Novo Brdo. Pyrgos fell into problems after the Battle of Maritsa in 1371, when the estates south of the Šar mountains fell under the rule of the Turks. The situation worsened when Prince Lazar took possession of Lipljan, because the Pyrgos’ monks did not comply with the agreement that they had to build defenses against the Turks, and stole the money and gifts the Prince had given them for this aim. The danger which threatened united the monks of the monastery and the pyrgos, and after the Battle of Kosovo, together they sake contribution from Princess Milica and her sons Stefan and Vuk. She accepted and donated villages in the area of Morava in the South-East of Kosovo. The documents does not provide information about what happened to the estates of pyrgos Chryseia in the fifteenth century. We think that they survived while the Lazarevic and Brankovic ruled in these parts, up to the year 1455.